Gender wage gap in China: a large meta-analysis - Ichiro Iwasaki; Xinxin Ma (Journal for Labour Market Research, 2020)
This paper performs a meta-analysis of 1472 estimates extracted from 199 previous studies to investigate the gender wage gap in China. The results show that, although the gender wage gap in China during the transition period has an impact that statistically significant and economically meaningful, it remains at a low level. It is also revealed that the wage gap between men and women is more severe in rural regions and the private sector than those in urban regions and the public sector. Furthermore, we found that, in China, the gender wage gap has been increasing rapidly in recent years.
Keywords: D63; J31; J71; P25; P36; 330; Gender wage gap; Meta-synthesis; Meta-regression analysis; Publication selection bias; China